Are Kidney-Tonifying and Blood-Activating Medicinal Herbs Better than NSAIDs for Knee Osteoarthritis? A Systematic Review and Meta-Analysis. (25th November 2019) - Huang, Hetao; Pan, Jianke; Yang, Weiyi; Han, Yanhong; Luo, Minghui; Liang, Haodong; Zeng, Lingfeng; Liang, Guihong; Lin, Jiongtong; Liu, Jun
Abstract : Objective . To compare the efficacy and safety of kidney-tonifying and blood-activating medicinal herbs (KTBAMs) and nonsteroidal anti-inflammatory drugs (NSAIDs) in the treatment of knee osteoarthritis (KOA). Methods . Randomized controlled trials (RCTs) from online databases that compared the efficacy of KTBAMs and NSAIDs in the treatment of KOA were retrieved. The main outcomes included the evaluation of functional outcomes, pain, and adverse effects. The Cochrane risk-of-bias (ROB) tool was used to assess methodological quality. Results . A total of 38 RCTs (3994 participants) were included in our meta-analysis. We found that KTBAMs had a significantly higher total effective rate (P < 0.00001, risk ratio (RR) = 1.08, confidence interval (CI) = 1.05 to 1.11, I 2  = 4%) and a lower gastrointestinal adverse reaction rate (P < 0.00001, RR = 0.36, CI = 0.24 to 0.53, I 2  = 33%) than NSAIDs. KTBAMs showed greater improvements in the Knee Society Scale (KSS) scores (mean difference (MD) = 7.17, 95% CI 0.71 to 13.64, P = 0.03 ). Regarding the visual analog scale (VAS) scores, WOMAC scores, and Lequence scores, there were no significant differences between the KTBAM group and the NSAID group. The GRADE quality level of this systematic review indicated that the very low-quality evidence showed that KTBAMs had a higher total effective rate, while the moderate-quality evidence showed that the adverse reactions of KTBAMs were lower and the KSS scores were higher. Low-quality evidence showed no significant differences in improving VAS scores, WOMAC scores, or Lequence scores. Conclusion . KTBAMs were superior to NSAIDs in terms of a higher total effective rate, a lower adverse reaction rate, and a higher KSS score. There were no significant differences between KTBAMs and NSAIDs in improving VAS scores, WOMAC scores, and Lequence scores of patients with KOA. Therefore, KTBAMs may be an alternative effective method for treating KOA. However, high-quality, well-designed RCTs with long-term follow-up are still required.